Формування кластерів за участю підприємств молочної промисловості - Ніколаєнко, Світлана Миколаївна (My University, 2023)
Досліджено, узагальнено та систематизовано теоретичні підходи до розуміння сутності поняття «кластер» та формування кластерів у світовій та національній економіці. На підставі аналізу наукових досліджень визначено економічну сутність кластеру. Розвинуто підходи до класифікації кластерів ознаками сфери суспільного життя, способу організації, стадій життєвого циклу, типу інтеграції. Доповнено класифікацію кластерів класифікаційною ознакою сфери діяльності, що дозволило доповнити існуюче групування кластерів поняттями «соціальний», «екологічний», «інноваційний», «змішаний кластер». Досліджено стан та результативність діяльності підприємств харчової промисловості, що дозволило виявити тенденції та закономірності їх розвитку, які проявляються у скороченні кількості підприємств, зміні структури виробництва, зменшенні кількості працюючих тощо. Застосування статистичного методу оцінювання потенціалу кластеризації на основі розрахунку коефіцієнтів локалізації, душового виробництва та спеціалізації дозволило виявити різну доцільність та потенційну можливість об'єднання підприємств в кластерні структури різних галузей харчової промисловості. На основі аналізу виявлено потенційну доцільність формування кластерів молочної промисловості на територіях Київської, Кіровоградської, Сумської, Черкаської, Харківської, Миколаївської, Полтавської, Хмельницької та Чернігівської областей. The theoretical approaches to understanding the essence of the concept of "cluster" and the formation of clusters in the world and national economy have been researched, generalized and systematized. Based on the analysis of scientific research, the economic essence of the cluster is determined. Approaches to the classification of clusters by features of the sphere of social life, method of organization, stages of the life cycle, type of integration have been developed. The classification of clusters was supplemented with a classification feature of the field of activity, which allowed to supplement the existing grouping of clusters with the concepts of "social", "ecological", "innovative", "mixed cluster". The state and effectiveness of food industry enterprises were studied, which made it possible to identify trends and patterns of their development, which are manifested in the reduction of the number of enterprises, changes in the structure of production, reduction in the number of employees, etc. The application of the statistical method of assessing the potential of clustering based on the calculation of the coefficients of localization, mass production and specialization made it possible to identify the various expediency and the potential possibility of combining enterprises into cluster structures of various branches of the food industry. Based on the analysis, the potential expediency of forming dairy industry clusters in the territories of Kyiv, Kirovohrad, Sumy, Cherkasy, Kharkiv, Mykolaiv, Poltava, Khmelnytskyi and Chernihiv regions was revealed. Approaches to the formation of clusters in the dairy industry have been formed, which reflect a certain sequence of mandatory actions, the implementation of which will ensure the achievement of the goal by solving the set tasks. The stages of forming a cluster association with the participation of dairy industry enterprises are summarized. Based on the results of the research, the priority types of clusters were determined. In order to evaluate the benefits of dairy industry enterprises joining clusters, a matrix of influence of cluster participants on reducing threats to the activities of the cluster initiator (dairy industry enterprises) was constructed. The application of the method of analysis of hierarchies made it possible to reveal different degrees of realization of the economic interests of dairy industry enterprises and agricultural milk producers in different types of clusters. An algorithm for forming a cluster structure was proposed, which made it possible to determine the optimal procedure for creating and functioning of a cluster. Generalized signs of identification of territorial, sectoral, agro-industrial and innovation clusters. A model of the dairy industry cluster of the Kyiv region has been formed. Сформовано підходи до формування кластерів в молочній промисловості, які відображають певну послідовність обов'язкових дій, реалізація яких забезпечить досягнення мети шляхом вирішення поставлених задач. Узагальнено етапи формування кластерного об'єднання за участю підприємств молочної промисловості. За результатами проведеного дослідження, визначено пріоритетні типи кластерів. Для оцінювання переваг входження підприємств молочної промисловості в кластери побудовано матрицю впливу учасників кластеру на зниження загроз діяльності ініціатора кластеру (підприємства молочної промисловості). Застосування методу аналізу ієрархій дозволило виявити різну міру реалізації економічних інтересів підприємств молочної промисловості та сільськогосподарських виробників молока в різних типах кластерів. Запропоновано алгоритм формування кластерної структури, який дозволив визначити оптимальний порядок створення та функціонування кластеру. Узагальнено ознаки ідентифікації територіального, галузевого, агропромислового та інноваційного кластерів. Сформовано модель кластеру молочної промисловості Київської області.
Keywords: кафедра обліку і аудиту; молочна промисловість; територіальний кластер; галузевий кластер; харчова промисловість; ефективність кластеру; формування кластеру; dairy industry; territorial cluster; industry cluster; food industry; cluster efficiency; cluster formation